Evaluasi Kinerja Usaha Petani Garam Rakyat di Kabupaten Bima, Nusa Tenggara Barat - Amril Rahman; Sapta Raharja; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
Flood of salt imports from the country four season to meet consumption needs and the needs of industry to Indonesia make the price of salt is low. Surprisingly rich tropical sea water and sunlight with the fourth longest coastline in the world's, but in 2010 national production of only 30,600 tons of salt or less than 1% of national demand,  because the harvest in a number of production centers 1.000-7.000 tons. Ponds area and one of the factors that influence the production of salt is an integral part of the performance of producing salt as salt producers nationwide. Business performance on a salt farmer folk analyzed the influence of the land area of ​​salt ponds on productivity, quality and financial performance by analysis of variance (Anova), for quality is conducted lab tests and analysis of financial performance using the calculation of revenue, R/C ratio and B/C ratio. The analysis showed no real productivity diversity. Salinity of sea water highest diversity in the people who produce the salt flats with an area of ​​0.23 acres of land with an average 4,576,666.67, the lowest score in the group of farmers with vast salt flat 0.85 acres of land with an average 1.6775 million. The analysis showed no real income diversity. R / C ratio and B/C ratio is generated providing the highest value in the group of people who produce salt area of ​​0.23 hectares with an average 10.1533, the lowest in the group of salt peasants with land area of 0.85 acres with a mean average of 3.2367. Effect of salt ponds land productivity, quality and financial performance analysis of variance analysis showed no significant difference, then the people's business performance by producing salt undervalued and needs to be increased by salt farmers.